The potential benefits of pet-facilitated therapy (Pft) in the juvenile delinquents - Zaw, Cho Cho; Ahmad, Norfadzilah; ., Myat Min @ Mohd Omar (SAS publisher, 2019)
Juvenile delinquents refer to young people of age eighteen years or younger who have committed a crime or antisocial acts such as vandalism, stealing the things, or violence against others. Seeking solutions to reduce juvenile delinquency is one of the important responsibilities among members of society. Numerous instances indicate that the pet animals are helpful for the youths who have difficult relationships with other people, cope with the emotions they experienced, improve their communication and social skills, and behave as a responsible citizen which helps to reduce crime rates and promote safe environment. Nonetheless, there are very few evidences of incorporating pet therapy into the community client care setting or rehabilitation center in Malaysia. Public as well as nurses, doctors, social workers and health care providers need to get awareness of pet therapy so that they would integrate it and the best use of it in dealing young people with antisocial behaviors or juvenile delinquents. Thus, the aim of this study is to explore the potential benefits of pet-facilitated-therapy (PFT) such as the importance and use of it, physical, mental, and social benefits of it among the juvenile delinquents. In this paper, all the available articles or studies regards to pet therapy in young people or adolescents are searched through electronic data bases using systematic literature search. The findings are categorized into three themes namely (i) important role of pets in adolescent development, (ii) the use of pet therapy in rehabilitation centre, (iii) physical, social and mental benefits of pet therapy in juvenile delinquents. This study provides strong evidence of the benefits of PFT and recommends the best use of it as part of the rehabilitation process of adolescents with antisocial behaviors or juvenile delinquents.